Study protocol: type II hybrid effectiveness-implementation study of routine functional status screening in VA primary care - Francesca M. Nicosia; Kara Zamora; LauraEllen Ashcraft; Gregory Krautner; Marybeth Groot; Bruce Kinosian; Cathy C. Schubert; Sumedha Chhatre; Helene Moriarty; Orna Intrator; Andrea Wershof Schwartz; Ariela R. Orkaby; et al. (Implementation Science Communications)
Abstract Background Maintaining functional status, defined as the ability to perform daily activities such as bathing, dressing, and preparing meals, is central to older adults’ quality of life, health, and ability to remain independent. Identifying functional impairments – defined as having difficulty or needing help performing these activities – is essential for clinicians to provide optimal care to older adults, and on a population level, understanding function can help anticipate service needs. Yet uptake of standardized measurement of functional status into routine patient care has been slow and inconsistent due to the burden posed by current tools. The goal of the Patient-Aligned Care Team (PACT) Functional Status Screening Initiative is to implement and evaluate a patient-centered, low-burden intervention to improve identification and management of functional impairment among older veterans in Veterans Health Administration (VHA) primary care settings. Methods We will conduct a hybrid type 2 implementation-effectiveness cluster-randomized adaptive trial at 8 VHA sites using the Practical, Robust Implementation and Sustainability Model (PRISM) to guide implementation and evaluation. During a Pre-Implementation phase, we will engage clinical partners and develop local adaptations to maximize intervention-setting fit. During an Implementation phase, we will launch a standard bundle of implementation strategies (coalition building, champions, technical assistance) and system-level audit and feedback, identify sites with low uptake, and randomize those sites to receive continued standard vs. enhanced strategies (standard strategies plus clinician-level audit and feedback). The primary implementation outcome is reach (proportion of eligible patients at each site who receive screening/assessment) and the primary effectiveness outcome is appropriate management of impairment (proportion of patients with identified impairments who receive related referrals). Discussion Implementing routine measurement of functional status in primary care has the potential to improve identification and management of functional impairment for older veterans. Improved management includes increasing access to services and supports for veterans and family caregivers, reducing potentially preventable acute care utilization, and allowing veterans to live in the least restrictive setting for as long as possible. Implementation will also provide data to inform the delivery of proactive interventions to prevent and delay development of functional impairment and improve quality of life, health, and independence. Trial registration Registered at ClinicalTrials.gov on May 7, 2024, at NCT06404970 ( https://clinicaltrials.gov/ ). Reporting guidelines Standards for Reporting Implementation Studies (Additional file 1).